38. Prolonged phone-call posture as risk factor for developing ulnar nerve entrapment at elbow: A dynamic neurophysiological study. Issue 4 (April 2016) - Coraci, D.; Padua, L.; Erra, C.; Doneddu, P.; Granata, G.; Rossini, P.M.
Abstract : Ulnar neuropathy at elbow (UNE) is often related to postures and work-hobby activities. The use of mobile-phones has drastically increased in the last decades leading to prolonged phone posture (PPP) with flexed elbow. We aimed to assess the effect of PPP in patients with symptoms of UNE and in symptom-free subjects. Patients with pure sensory symptoms of UNE and negative neurophysiological tests (min-UNE) and symptoms-free subjects were enrolled. We evaluated ulnar motor nerve conduction velocity across elbow at baseline and after 6, 9, 12, 15, 18 min of PPP. Thirty-eight symptom-free subjects and thirty-eight patients were enrolled and 121 ulnar nerves were studied. Conduction velocity of ulnar nerve across the elbow significantly changed over PPP time both in control group and, at a greater extent, in patients with min-UNE. Conduction velocity during PPP showed different evolution between the two groups. The changes became significantly different after 6 min of PPP and progressively increased, with the greatest difference at 15 min. In conclusion, PPP causes a modification of nerve function, expressed by slowing of motor nerve conduction velocity, which is greater in patients with min-UNE although it also occurs in symptom-free subjects. Excessive PPP should be avoided in patients with UNE-symptoms.